PENINGKATAN MINAT MENGIKUTI KEGIATAN EKSTRAKURIKULER MELALUI LAYANAN BIMBINGAN KELOMPOK PADA SISWA VII G VII I DAN VII J SMP NEGERI 16 SURABAYA - Nurzaki Alhafiz (Jurnal Inovasi Penelitian, 2021)
Students should be able to take advantage of extracurricular activities for their self-development. However, in reality what is happening in the field is the lack of interest of students to take advantage of extracurricular activities. This study aims to determine whether group guidance can increase student interest in extracurricular activities. The technique used in this research is action research techniques in counseling guidance (PTBK) or also known as action research. This study consisted of two cycles and each cycle had four stages, namely: planning, implementing the action, observing and reflecting. This research was conducted in 16 Junior High School, Surabaya, East Java Province. The population in this study were students in the research class, namely class VII G, VII I, and VII in the 2016/2017 academic year. Samples were taken using purposive sampling technique and obtained as many as one group of 8 people, consisting of 5 men and 3 women. This research uses descriptive analysis of quantitative data as well as qualitative data that has been collected. The findings of this study are the use of group guidance techniques can increase interest in extracurricular activities